Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.